The spatial patterns of diversity and their relationships with environments in rhizosphere microorganisms and host plants differ along elevational gradients - Xu, Shijia; Yuan, Yan; Song, Pengfei; Cui, Mufeng; Zhao, Rensheng; Song, Xiaoyang; Cao, Min; Zhang, Yazhou; Yang, Jie (Frontiers in Microbiology, 2023)
Identifying spatial patterns of biodiversity along elevational gradients provides a unified framework for understanding these patterns and predicting ecological responses to climate change. Moreover, microorganisms and plants are closely interconnected (e.g., via the rhizosphere) and thus may share spatial patterns of diversity and show similar relationships with environments. This study compared diversity patterns and relationships with environments in host plants and rhizosphere microorganisms (including various functional groups) along elevational gradients across three climatic zones. We found that above- and belowground diversity decreased monotonically or showed a hump-shaped or U-shaped pattern along elevation gradients. However, the diversity patterns of plants, bacteria, and fungi varied depending on the taxon and climatic zone. Temperature and humidity strongly contribute to above- and belowground diversity patterns and community composition along elevational gradients. Nonetheless, soil factors might be important regulators of diversity patterns and the community composition of plants and microorganisms along these gradients. Structural equation modelling revealed that environmental factors had a stronger direct effect on rhizosphere microbial diversity than host plant diversity. In sum, spatial patterns of diversity and their relationships with environments in rhizosphere microorganisms and their host plants differed at the regional scale. Different functional groups (e.g., pathogen, mycorrhiza and nitrifier) of soil microorganisms may have divergent elevational patterns and environmental responses. These data improve our understanding of elevational diversity patterns, and provide new insights into the conservation of biodiversity and ecosystem management, especially under climate change.